The mediating effect of work burnout in the relationships between job demands and job performance of business educators - James Edokpolor; Henry Okosun; Adesuwa Imafidon; Adeolu Olatoye (Insight: Jurnal Ilmiah Psikologi, 2024)
Following the postulations of the Job Demands-Resources (JD-R) theory and the Conversation of Resources (COR) theory, this study examined the relationships between job demands and job performance of business educators with work burnout as a mediator. A nonexperimental quantitative research design was used to achieve the specific purpose of the study. The participants consisted of 142 business educators (12 HODs and 130 lecturers). The instruments for data collection was a structured questionnaire, adapted from existing psychological scales. The instruments were validated by three experts, two in Business Education and one in Measurement and Evaluation. Cronbach’s alpha was used to obtain the reliability values for each scale: job demands (α = 0.84), work burnout (α = 0.73) and job performance (α = 0.95). Data collected were analyzed using Pearson’s correlation, linear regression and bias corrected and accelerated regression statistics. The findings revealed that job demands positively predicted work burnout and negatively predicted job performance; work burnout negatively predicted job performance, and work burnout significantly mediated the relationships between job demands and poor job performance. The authors recommended, among others, that university managers and administrators should endeavour to create a conducive, resourceful and motivated working environment as this will provide opportunity for business educators to surmount work burnout, which would eventually lead business educators to perform effectively on the job. Keyword: Business educators; job demands; job performance; public Universities; work burnout.